Ethnobotanical investigations and urban utilization potential of medicinal and edible Lamiaceae plants: a case study from Guizhou, China - Yang, Mengxue; Wu, Huan; Geng, Yanfei (Frontiers in Pharmacology, 2025)
IntroductionThe unique geographical environment of Guizhou Province, China, has nurtured rich resources of Lamiaceae. The Dong people have developed diverse medicinal and edible utilization methods for Lamiaceae plants through long-term practice. This study mainly aims to (1) document the medicinal and edible uses of Lamiaceae plants in the Dong community of Yangwei Village, Shangzhong Town, Liping County, Guizhou; (2) evaluate the chemical composition of five Lamiaceae species; and (3) provide a detailed account and assessment of the tea-making process of Elsholtzia rugulosa, a commonly used local plant, while exploring its potential for development as a specialty tea beverage.Material and methodsYangwei Village (Liping County), a representative Dong ethnic community with rich ethnobotanical knowledge of medicinal and edible plants, was selected as main study site. Ethnobotanical knowledge of Lamiaceae plants was collected through semi-structured interviews with key informants and participatory observations. Five Lamiaceae plants were chemically analyzed, with E. rugulosa selected as the primary research subject due to its traditional applications, rich bioactive compounds, and good processing adaptability. The processing workflow of E. rugulosa tea was thoroughly investigated, with improvements based on standard green, oolong, and black tea procedures. The resulting three flavored tea broths were then subjected to sensory and compound evaluations.ResultsThe survey documented 101 Lamiaceae species (39 genera), mostly herbs. Chemical analysis indicated significant development potential for Prunella vulgaris, Leonurus japonicus, and Perilla frutescens. Sensory evaluation showed optimized E. rugulosa infusions had translucent color, pure aroma, and mellow taste. The black tea flavored infusion exhibited higher total phenolics and flavonoids; the oolong tea flavored infusion excelled in free amino acids and dry matter; and the green tea flavored infusion contained the highest water extract. The optimized E. rugulosa tea enhanced taste and preserved bioactive compounds, aligning with the urban demand for health, naturally derived, and culturally meaningful beverage products.ConclusionThe findings documents Dong-specific ethnobotanical knowledge in Yangwei Village Lamiaceae plants, which is valuable for both conservation and sustainable use. The medicinal plants from the Lamiaceae family have significant development potential, especially in urban use and commercialization.